Perancangan Identitas Visual Media Promosi Pada Brand Bakery Bite Bali - Natabuana, Nugraha; Nuriarta, I Wayan; Wibawa, Arya Pageh (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
Bite Bali is a bakery & dessert cafe from Bali located on Sunset Road, Seminyak, Badung. The competitor is quite tight with a similar business concept, Bite Bali has its own advantages and uniqueness, namely their special menu of pastry croissants with various choices of flavors. Not only the menu, the interior design of the Bite Bali shop is also no less interesting to visit. However, all of this uniqueness is considered insufficient to compete with other competing brands which are increasingly emerging with the same business concept. The Bite Bali brand has shortcomings in terms of visual branding, such as colors, typography and illustrations that do not yet have a consistent visual brand identity. Therefore, it is necessary to design a strong visual identity for the Bite Bali brand to further strengthen their brand awareness so that it has a distinctive image. This will help to build customer perceptions of the Bite Bali brand to be stronger, easier to remember and known and able to compete with other competitors. This project uses Alina Wheeler's creation method with five stages of conducting research, clarifying strategy, designing identity, creating contact points, and managing assets. The data collection technique using a qualitative descriptive method, namely collecting data through four methods, namely interviews, observation, documentation and literature study. This project produces a brand's visual identity, such as logo, colors, typography and illustrations. After that, the brand's visual identity is consistently applied to the required commercial media design such as posters, menus, loyalty cards, stickers and social media content.